2013
DOI: 10.1007/s00421-013-2689-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high vs. moderate exercise intensity during interval training on lipids and adiponectin levels in obese young females

Abstract: The results show that HIIT positively changes blood lipids and adiponectin variables in obese adolescent girls, resulting in improved insulin sensitivity, as attested by a lower HOMA-IR, and achieving better results compared to moderate-intensity exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
341
9
19

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(392 citation statements)
references
References 43 publications
23
341
9
19
Order By: Relevance
“…They found that physical activity was not significantly associated with adiponectin, while vigorous physical activity showed a significant inverse association with adiponectin after adjusting for age, sex, pubertal status and abdominal circumference [14]. High-intensity interval training positively changed adiponectin levels in obese adolescent girls [18]. In addition, circulating adiponectin levels were correlated with body weight, BMI, triglyceride and HDL cholesterol as previously reported [30,31].…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…They found that physical activity was not significantly associated with adiponectin, while vigorous physical activity showed a significant inverse association with adiponectin after adjusting for age, sex, pubertal status and abdominal circumference [14]. High-intensity interval training positively changed adiponectin levels in obese adolescent girls [18]. In addition, circulating adiponectin levels were correlated with body weight, BMI, triglyceride and HDL cholesterol as previously reported [30,31].…”
Section: Discussionsupporting
confidence: 53%
“…Several studies in the literature regarding the relationships between circulating adiponectin levels and physical activity and/or physical fitness have been reported [14][15][16][17][18][19][20][21][22]. However, the link between circulating adiponectin levels and physical activity and/or peak oxygen uptake independent of body composition has not fully discussed in Japanese.…”
Section: Introductionmentioning
confidence: 99%
“…Twelve weeks of interval training in obese young females increased adiponectin which was coincident with significant reductions in body mass, %BF, and insulin concentration. 60 In the SCI, only one study to our knowledge examined changes in adiponectin in response to training. Rosety-Rodriguez et al 61 separated 17 men with paraplegia into a control or exercise (12 weeks of arm cranking) group.…”
Section: Igf-i Was Unchanged With Training Although Therementioning
confidence: 99%
“…It has been proposed that chronic high-intensity interval training (HIIT) (≈85% VO 2max ) may elicit greater health benefits than traditional chronic aerobic exercise. Reasons for this supposition include improvements in SOD activity [11], aerobic capacity [15], blood lipids [16], and blood pressure [17] that are more remarkable when exercise is performed at higher intensities.…”
Section: Introductionmentioning
confidence: 99%